The Situation of Cross-Border Transportation of Goods through the 2nd Friendship Bridge Savannakhet-Mukdahan: https://doi.org/10.69692/SUJMRD1001141 - XAYYALATH, Kaysone; SOMBOUNSACK, Phoumsaydavone; PHOTHISALATH, Vilaphon (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This study is about the situation of cross-border transportation of goods through the 2nd Friendship Bridge Savannakhet-Mukdahan. The purpose of the study is to 1) study the situation of development of transportation and logistics in the friendship bridge, 2) The condition of transporting goods through the friendship bridge, and 3) Difficulties of entrepreneurs using the 2nd friendship bridge service, the population represented in the study was the driver of a truck that passed through the Savannakhet-Mukdahan International Checkpoint, Specific types of imported goods a total of 138 people were identified. The statistics used for data analysis is descriptive statistics to find frequencies and percentages. The results of the study show that the world bank has determined the logistics performance index: LPI and published the results of the comparative efficiency ranking of 160 countries. In 2018, the Lao PDR was ranked 82nd in the world with a score of 2,8 and in which ranked 69th of 160 counties in terms of the ability to trach and trace consignments with an average score of 2,9. Laos can now export and distribute goods to Thailand with other countries in Asia and Europe: China, Hungary, Poland, Belgium, the Netherlands, Singapore, Japan, Italy and France using Road NO 12 and Route 9. This is an important strategic route due to the ability to transport goods to countries in the region, which is a wholesale market and a channel to import cheap machinery, equipment, or inputs, making locally produced goods cheaper, which will increase domestic competitiveness and increase domestic competitiveness. Exports and imports across the 2nd Friendship Bridge, a five-year period from 2016-2020, see a year-on-year trade deficit due to the need to use agricultural inputs to boost agricultural production and boost agricultural exports in the future. The problems in transportation of goods in practice, the country has not yet been able to take full advantage of cross-border transport via the 2nd Friendship Bridge. Due to climate change, which is a barrier to delayed transportation, the overall infrastructure is still incomplete as there are still some areas of the road that need to be constructed and improved, along with the problems and obstacles of transport rules and regulations, such as: Problems with one-stop inspection, difficulties in customs clearance procedures and convenience of transport officials.